Continuous dynamic monitoring of an onshore wind turbine. (1st June 2018) - Oliveira, Gustavo; Magalhães, Filipe; Cunha, Álvaro; Caetano, Elsa
Highlights: Continuous monitoring of acceleration data from an 2 MW wind turbine during one year. Innovative strategy for application of modal identification methods to wind turbines. Identification of the modal properties of the main wind turbine vibration modes. Characterization of natural frequencies and damping ratios of the first bending modes. Abstract: Current utility-scale wind turbines are highly dynamic systems excited by a large variety of loading sources. The proper operation of wind turbines thus requires a complete knowledge of the actual dynamic behavior of the system, in order to ensure the expected longevity of their main structural elements. In that context, this paper describes the monitoring project developed for a 2.0 MW wind turbine, the description of the installed monitoring system, as well as the main steps included in the methodology developed for the continuous processing of the collected data. The main results achieved during one year of monitoring are shown in detail. They allowed to accurately characterize the variability of the dynamic properties of the wind turbine, with special emphasis on the natural frequencies and damping ratios of the most important vibration modes, throughout normal operating conditions of the turbine. In addition, several shutdown events were identified and used to estimate the modal damping of the wind turbine through the analysis of free-decay responses of the structure. This monitoring project contributes to improve the knowledge on the dynamic behavior of onshore wind turbines under normal operating conditions.